Blood oxygenation level-dependent (BOLD) MRI of human skeletal muscle at 1.5 and 3 T - Partovi, Sasan; Jacobi, Björn (Journal of magnetic resonance imaging, 2012)
Purpose: To evaluate the dependence of skeletal muscle blood oxygenation level-dependent (BOLD) effect and time course characteristics on magnetic field strength in healthy volunteers using an ischemia/reactive hyperemia paradigm. Materials and Methods: Two consecutive skeletal muscle BOLD magnetic resonance imaging (MRI) measurements in eight healthy volunteers were performed on 1.5 T and 3.0 T whole-body MRI scanners. For both measurements a fat-saturated multi-shot multiecho gradient-echo EPI sequence was applied. Temporary vascular occlusion was induced by suprasystolic cuff compression of the thigh. T2* time courses were obtained from two different calf muscles and characterized by typical curve parameters. Ischemia- and hyperemia-induced changes in R2* (ΔR2*) were calculated for both muscles in each volunteer at the two field strengths. Results: Skeletal muscle BOLD changes are dependent on magnetic field strength as the ratio ΔR2*(3.0 T)/ΔR2*(1.5 T) was found to range between 1.6 and 2.2. Regarding time course characteristics, significantly higher relative T2* changes were found in both muscles at 3.0 T. Conclusion: The present study shows an approximately linear field strength dependence of ΔR2* in the skeletal muscle in response to ischemia and reactive hyperemia. Using higher magnetic fields is advisable for future BOLD imaging studies of peripheral limb pathologies. J. Magn. Reson. Imaging 2012;35:1227-1232. © 2012 Wiley Periodicals, Inc.
First published: 13 January 2012
Gesehen am 26.06.2018